The mobile middle: Indian skilled migrants in Singapore and the 'middling' space between migration categories. Issue 1 (1st March 2017) - Baas, Michiel
Studies of skilled migration tend to be strongly bifurcated in terms of their focus on either low- or highly-skilled migrants, and public debate generally also reflects this. However, since skills, education and income levels are frequently conflated, there are usually considerable differences in terms of how low or highly skilled migrants actually are. In addition, there has been little attention paid to strategies of mobility between various visa categories. This article focuses on what it conceptualizes as the 'mobile middle': skilled migrants who actively negotiate and test the flexibilities of a migration programme in order to be able to work and potentially stay on 'permanently' in a particular country. Drawing on ethnographic fieldwork among Indian (mid-level) skilled migrants in Singapore, the present study explores how we can (further) conceptualize migration categories, and the ways migrants engage with them with respect to inherent constraints on the one hand and ambitions for the future on the other. With its focus on Singapore, the article also highlights how the mobile middle, as a rapidly growing group of migrants, takes up an increasingly prominent place in discussions about new immigrants and population growth.